ANALISIS PENGEMBANGAN PEGAWAI DALAM MENINGKATKAN KUALITAS KERJA PADA PT. BANK MUAMALAT INDONESIA CABANG PEMATANGSIANTAR - M Fauzan (Jurnal At-Tabayyun, 2018)
This research was conducted to determine the effect of employee development on the quality of work at PT. Bank Muamalat Indonesia Branch Pematangsiantar and to find out which development variables most influence the quality of work at PT. Bank Muamalat Indonesia Branch Pematangsiantar. This research data uses primary data which is data obtained from respondents by giving questionnaires / questionnaires to employees of PT. Bank Muamalat Indonesia Branch Pematangsiantar and secondary data is data obtained by collecting data related to this research from PT. Bank Muamalat Indonesia Pematangsiantar branch and literature books. Primary data collected in this study were obtained through questionnaire techniques or questionnaires containing statements submitted in writing to the respondent to obtain answers and information needed in this study. In addition, primary data can also be obtained through interview techniques to research and observation informants, PT. Bank Muamalat Indonesia Branch Pematangsiantar is addressed at the Megaland Complex Blok A Jl. Sangnawaluh No. 6-7, Pematangsiantar North Sumatera. The results showed the participant variables, instructor variables and material variables partially showed a positive and significant effect on the variable quality of work. Material variables are the most dominant employee development variables in influencing the quality of employee work. Facility variables partially do not have a positive and significant effect on the variable quality of work. The dependent variable is the quality of work that is able to be explained by the independent variables namely facility, material, instructor and participant variables (67,7%) and the rest (32,3%) are explained by other variables outside the variables used.